1974
DOI: 10.1037/h0036215
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of psychological androgyny.

Abstract: This article describes the development of a new sex-role inventory that treats masculinity and femininity as two independent dimensions, thereby making it possible to characterize a person as masculine, feminine, or "androgynous" as a function of the difference between his or her endorsement of masculine and feminine personality characteristics. Normative data are presented, as well as the results of various psychometric analyses. The major findings of conceptual interest are: (a) the dimensions of masculinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

101
4,320
20
387

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 7,150 publications
(4,948 citation statements)
references
References 4 publications
101
4,320
20
387
Order By: Relevance
“…In addition, there is evidence that women have become more similar to men on a variety of other agentic traits over time, such as assertiveness (Twenge, 2001) and masculinity or instrumentality (Twenge, 1997). Twenge's (1997) meta-analysis that examined Bem's sex role inventory (BSRI; Bem, 1974) found that women's scores on the masculine (i.e., agentic) scale of the BSRI increased over time, and that gender differences on the masculine scale decreased over time. Concurrently, men did not increase in femininity, and gender differences in femininity remained stable (Twenge, 1997).…”
Section: Women's Change In Narcissism Over Timementioning
confidence: 99%
“…In addition, there is evidence that women have become more similar to men on a variety of other agentic traits over time, such as assertiveness (Twenge, 2001) and masculinity or instrumentality (Twenge, 1997). Twenge's (1997) meta-analysis that examined Bem's sex role inventory (BSRI; Bem, 1974) found that women's scores on the masculine (i.e., agentic) scale of the BSRI increased over time, and that gender differences on the masculine scale decreased over time. Concurrently, men did not increase in femininity, and gender differences in femininity remained stable (Twenge, 1997).…”
Section: Women's Change In Narcissism Over Timementioning
confidence: 99%
“…Isso pode ter se refletido nos estudos de Bem (1974) e Sabo (1985), nos quais as meninas possuem dificuldade de conciliar a natureza competitiva com a sua feminilidade. Da mesma forma, Eccles et al (1999) e Harrison e Lynch (2005) relatam que muitas jovens mulheres ainda acreditam existir um conflito inerente entre valores e preferências femininas com a grande competitividade que algumas atividades físicas proporcionam, características predominantemente masculinas.…”
Section: Discussionunclassified
“…Por outro lado, mulheres empenhadas na prática de esportes considerados masculinos recebem similar percepção de desvio. (BEM, 1974;COLLEY;CHIPPS, 1985;SABO, 1985;MESSNER;SABO, 1994;BRADY et al, 1996;ECCLES et al, 1999;HARRISON;LYNCH, 2005).…”
Section: Palavras-chaves: Esporte; Identidade De Gênero; Masculinidadunclassified
“…These differentiated responses can be observed in gender studies (Bem, 1974(Bem, , 1975(Bem, , 1977Heilbrun, 1976;Lorr & Maning, 1978;Silvern & Ryan, 1979), more specifically in studies that deal with psychological androgyny, as well as the studies by Helgeson (1994), in which she reported that individuals who possessed agentic and communal traits presented lower disease incidences than other individuals.…”
mentioning
confidence: 89%
“…In social psychology, a quick review reveals a series of contemporary theories in which opposites are present: (a) at the cultural level, in studies dealing with individualism versus collectivism (Triandis, 1989) and (b) at the individual level, in idiocentric self versus allocentric self (Triandis, Leung, Villareal, & Clack, 1985); in individual versus social identity (Banaji & Prentice, 1994); in the independent self versus the interdependent self (Markus & Kitayama, 1991); agency versus communion (Helgeson, 1994); and masculinity versus femininity (Bem, 1974;Constantinople, 1973;Feather, 1978;Heilbrun & Pitman, 1979;Orlofsky, 1977;Spence, Helmreich, & Stapp, 1975). In all these themes, opposites assume both an oppositional and complementary posture.…”
mentioning
confidence: 99%